Interactive visual machine learning in spreadsheets - Sarkar, Advait; Jamnik, Mateja; Blackwell, Alan F; Spott, Martin (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), 2015)
BrainCel is an interactive visual system for performing general-purpose machine learning in spreadsheets, building on end-user programming and interactive machine learning. BrainCel features multiple coordinated views of the model being built, explaining its current confidence in predictions as well as its coverage of the input domain, thus helping the user to evolve the model and select training examples. Through a study investigating users’ learning barriers while building models using BrainCel, we found that our approach successfully complements the Teach and Try system to facilitate more complex modelling activities.